Pengaruh Literasi Digital Dan Financial Literacy Terhadap Kesiapan Gen Z Menjadi Investor Pemula - Nasir, Adrian; Saputra, Dian Sidiq; Yeni, Hari (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study aims to analyze the effect of investment knowledge and technological advancement on Generation Z students’ investment decisions, with investment interest as an intervening variable. Generation Z, who grew up in the digital era, has broad access to financial information and financial technology, making knowledge and technology important factors in the investment decision-making process. This research employs a quantitative approach using path analysis. The research sample consists of 100 students from the Management Study Program at Universitas Negeri Makassar, selected using a specific sampling technique. The results indicate that investment knowledge and technological advancement have a significant effect on students’ investment interest. Furthermore, both variables also have a direct and significant influence on investment decisions. Investment interest is proven to mediate the effect of investment knowledge and technological advancement on the investment decisions of Generation Z students. These findings emphasize the importance of improving financial literacy and utilizing digital technology to encourage greater investment interest and more effective investment decision-making among students.